ANALISIS KINERJA DAN TINGKAT KESEHATAN PERUSAHAAN UMUM DAERAH (PERUMDA) AIR MINUM KOTA MAGELANG TAHUN 2017-2020 - Kulsum, Umi; Retnosari (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2023)
This study aims to assess the company's performance by analyzing financial aspects, service aspects, operational aspects, and human resource aspects at the Regional Public Company (Perumda) Water Drinking Magelang City. The performance assessment at the company has the aim of seeing and measuring the level of management performance in managing the BUMD and knowing the level of effectiveness and efficiency of management. The research method used is descriptive quantitative by using secondary data obtained from the financial statements of the Perumda Water Drinking Magelang City. This study uses data documentation techniques obtained from the financial statements of the Magelang City Water Company. The analysis used is an analysis of financial performance and non-financial performance based on the SPAM Implementation Improvement Agency (BPPSPAM) as a Non-Structural Institution at the Ministry of Public Works and Public Housing. The results of the calculation of the analysis of financial aspects, service aspects, operational aspects, and human resource aspects at the Perumda in Magelang City show a healthy level of performance. This shows that the Magelang City Water Supply Corporation has performed well.